A rheostat mechanism governs the bifurcation of carbon flux in mycobacteria - Paul Murima (Nature Portfolio, 2016)
Microbes survive in dynamic environments by modulating their intracellular metabolism. Here, the authors reveal that mycobacteria employ a rheostat-like mechanism to regulate carbon flux between the oxidative TCA cycle and the glyoxylate shunt during glucose-acetate diauxic shift.